Modelo didático de um motor 2 tempos a partir de um compressor de refrigerador - Silva, Jadson Jácome da (Universidade Federal Rural do Semi-Árido, 2019)
Considering that the didactic tools help in the students' learning, because it allows a better view of the theory, and noting the difficulty that students of the technical and superior courses in engineering have to assimilate the operation of thermal machines, in particular, the combustion engines internal, and since there is often no access to the tools in practice due to its high cost, the present work consists of a manual that can help teachers and students in the construction of their own didactic models, serving as the basis for the theoretical classes , where it can address the history, characteristics, and operation of a thermal machine. The prototype was made from a refrigerator compressor, already the basis for the ignition system (SI), was used a flyback of TV set, which can achieve the required high voltage, in the development of the work information on the process of creating the prototype, exposing them materials used to make it as simple and cheap as possible. Parts such as capacitive discharge ignition system and platinum, which are generally difficult to access to small cities, or their market prices are very high, the model fits perfectly in the parameters and characteristics of a thermal machine, and the objective was achieved.
Monografia
Keywords: Motores a Combustão interna; Protótipo; Didático; Internal Combustion Engines; Prototype; Didactic; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA